Implementation of the SIAKBA Application Sub-District Election Committee Admission Committee at the Semarang City General Election Commission - Mita Wulandari; Yuwanto; Nunik Retno Herawati (PERSPEKTIF, 2023)
The sophistication of information technology that continues to grow is utilized by election organizers (KPU) by building an Information System for Members of the General Elections Commission and the Adhoc Agency (SIAKBA). To carry out the process of accepting the Subdistrict Election Committee as stated in the General Election Commission Regulation Number 8 of 2022 concerning the Formation and Work Procedure of Adhoc Bodies in holding the 2024 elections. This research is intended to find out how SIAKBA is implemented in accepting Adhoc bodies at the sub-district level. The method used in this research qualitative method with a descriptive approach. Data collection techniques were obtained from the field (interviews, observation and documentation). From the results of the research using Edward III's theory, it was concluded that the KPU of Semarang City is ready to carry out the recruitment of Adhoc bodies for PPK members through SIAKBA. Through very good communication patterns, very supportive resources, the disposition or attitude of the SIAKBA team in accepting applicants is full of commitment, responsibility and is ready to carry out all stages of recruitment based on the rules and norms that apply.